2011
DOI: 10.1021/ja110224d
|View full text |Cite
|
Sign up to set email alerts
|

Radical Chain Reduction of Alkylboron Compounds with Catechols

Abstract: The conversion of alkylboranes to the corresponding alkanes is classically per-formed via protonolysis of alkylboranes. This simple reaction requires the use of severe reaction conditions, that is, treatment with a carboxylic acid at high temperature (>150 °C). We report here a mild radical procedure for the transformation of organoboranes to alkanes. 4-tert-Butylcatechol, a well-established radical inhibitor and antioxidant, is acting as a source of hydrogen atoms. An efficient chain reaction is observed due … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
66
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 88 publications
(71 citation statements)
references
References 62 publications
5
66
0
Order By: Relevance
“…[12] Thec oupling of tertiary boronic ester 1p proved to be more challenging,t he increased steric hindrance imposing anegative effect on the final oxidation step.Specifically,only one of the two diastereomers of 2p was converted into furan product 3p (32 %y ield from RBpin) under the standard reaction conditions.W et herefore investigated alternative oxidants and found that Cu(OAc) 2 was able to oxidize both diastereomers of 2p and gave the product 3p in an improved yield (41 %). [13] Thec ontrasting behavior of the two diastereomers warranted further investigation, which was conducted with the achiral tert-butyl-Bpin. As before,o ne diastereomer was rapidly oxidized to the desired product 3q leaving behind the unreactive diastereomer 2q,w hich was fully characterized.…”
Section: Angewandte Chemiementioning
confidence: 99%
“…[12] Thec oupling of tertiary boronic ester 1p proved to be more challenging,t he increased steric hindrance imposing anegative effect on the final oxidation step.Specifically,only one of the two diastereomers of 2p was converted into furan product 3p (32 %y ield from RBpin) under the standard reaction conditions.W et herefore investigated alternative oxidants and found that Cu(OAc) 2 was able to oxidize both diastereomers of 2p and gave the product 3p in an improved yield (41 %). [13] Thec ontrasting behavior of the two diastereomers warranted further investigation, which was conducted with the achiral tert-butyl-Bpin. As before,o ne diastereomer was rapidly oxidized to the desired product 3q leaving behind the unreactive diastereomer 2q,w hich was fully characterized.…”
Section: Angewandte Chemiementioning
confidence: 99%
“…Although this strategy had been applied to benzylic carbamates, the resulting benzylic boronic esters (where boron is adjacent to functionality) are very easily protodeboronated simply with TBAF·3H 2 O (TBAF, tetra-N-butylammonium fluoride), so the strategy is not generally applicable 9-12 . The major challenge in realizing this strategy is the protodeboronation of the more-stable secondary alkyl pinacol esters, remote from any functionality (for example, 3 → 4), as there were no known methods for achieving such a transformation directly, although there were methods for carrying out the overall transformation indirectly 13,14 . In this paper we describe a new protocol for protodeboronation and its tactical use in conjunction with lithiation-borylation as a new strategy for assembling molecules without trace of the functional groups used in their genesis.…”
mentioning
confidence: 99%
“…The oxidation of emodin ( 9 ) gave the benzophenone intermediate (structure i ), which could further transform into diphenyl ether derivatives ( 7 and 8 ) via grisendience1516. Generated by i and 8 17, intermediate ii could afford compound 1 − 3 through an aldol condensation as well as the additional esterification. In addition, 4 and 5 were transformed from intermediate iii by esterification and reduction, which was a reductive product of intermediate i .…”
Section: Resultsmentioning
confidence: 99%